PENGARUH LINGKUNGAN MASYARAKAT DAN KEPRIBADIAN SISWA TERHADAP PERILAKU KEAGAMAAN SISWA SMP ASSAHAQIAH BEKASI - Ahmad Hotib HS; Fahmi Sahlan; Adi Rahman (Almarhalah, 2022)
The community environment has a huge influence on children's development, especially in the behavior and personality of students. Personality is a mechanism that controls and directs a person's attitudes and behavior. If a person's personality is strong, then his attitude is firm, not easily influenced by the persuasion of factors that come from outside. Conversely, if the personality is weak, then a person will be easily swayed by various external factors and influences. Religious attitude is a condition that exists within a person who encourages him to behave according to his level of religious observance. The condition found at SMP Assahaqiyah Bekasi is that students still have weak personalities, as evidenced by their attitude when religious activities take place such as congregational prayers, they still need a warning from the teacher.The approach used in this research is a quantitative approach. Data was collected through questionnaires and documentation. The data analysis technique used was simple linear regression and multiple linear regression analysis. The population in this study were all students of SMP Assahaqiyah Bekasi which consisted of 3 classes totaling 40 children. And the sample used was 40 students.Based on the data analysis conducted, the research can conclude that there is a relationship between the community environment and religious behavior shown by thit of 3.854 and p-value 0.000 0.05, so H0 is rejected. Thus the community environment has a positive effect on religious behavior. The results of the study concluded that the relationship between students' personality and religious behavior indicated by thit was 3,057 and p-value 0.004 0.05, so H0 was rejected. Thus the student's personality has a positive effect on religious behavior.The results of the study concluded that when viewed from table B, the value of = 13,243 + 0.398 X1 + 0.457 X2. Seen in column sig 0.000 compared to alpha 0.05 the result is smaller, so H0 is rejected. Thus the better the community environment and the personality of students together they influence religious behavior. So, the influence of the community environment and the personality of students simultaneously both affect religious behavior by 56.5%. Keywords: Community Environment, Personality, Religious Behavior